Improving Development Strategy of Budgetary Institution - A. V. Borodin (Здоровье мегаполиса, 2024)
Background. In a competitive environment, budgetary healthcare institutions have less management tools and technologies than private organizations. Budgetary institutions are  able  to  compete  in  providing  advanced medical care, but not in attracting and retaining highly qualified workers.In addition, budgetary institutions have access to growing financial resources and untapped instruments, especially management technologies applied in commercial organizations. Some principles and methods of corporate governance can be implemented in the management processes of budgetary institutions in order to increase their competitiveness and performance.Purpose. To analyze the current planning of financial and operating activities at a budgetary institution and to make recommendations for expanding the managerial and commercial components in the planning of activities.Materials and methods. The comparative analysis was carried out to contrast budgetary healthcare institutions with private medical organizations in planning and management technologies used in commercial organizations and other industries. This method enabled to identify general trends and features in the management of healthcare organizations. Also, Russian full-text sources and regulatory documents on the research topic were studied using content analysis method.Conclusion. In a competitive environment and under an insufficient budget financing, it is necessary to expand the tools for planning financial and operating activities in non-profit medical institutions and the authorities of budgetary institutions’ heads.